Musical communication, emotion regulation and the capacity for attention control: A theoretical model. (November 2014) - Swaine, Joel S.
In music psychology, studies of emotion regulation are typically about the self-regulation of emotion in, primarily, music listeners. What is missing from the literature is a model of emotion regulation that accounts for both intrinsic (self-generated) and extrinsic (other-generated) processes, which could inform an understanding of how music can be used by one person to extrinsically influence emotion regulation in another. To address this gap, the present article develops a theoretical model of musical communication. Musical communication is conceptualized as a goal-directed process in which one musical participant (the therapist) influences the emotion regulation strategies employed by another (the client). The theory proposes that an important goal of musical communication is to encourage clients to regulate their emotional responses in ways that enhance rather than diminish their capacity to sustain attention. This goal is proposed to be pursued by enabling clients to exercise their ability to sustain attention, and by promoting three processes that serve to enhance their attentional capacity: the utilization of emotional arousal to facilitate sensory processing, the facilitation of emotional motor tendencies, and the reduction of behavioural uncertainty. These propositions are analysed and discussed with a focus on emotion regulation in worry-prone clients.